2016
DOI: 10.1037/sgd0000162
|View full text |Cite
|
Sign up to set email alerts
|

Sexual minority students in non-affirming religious higher education: Mental health, outness, and identity.

Abstract: Sexual minority (SM) students are vulnerable to increased rates of psychological distress and harassment as a result of stigma and other forms of marginalization in the college environment. However, little research has been conducted on the experiences and psychological functioning among SMs who attend nonaffirming religiously affiliated universities (NARAUs) that enforce restrictive admission and conduct policies toward SM students, and/or view same-sex romantic expressions and identities as sinful. SM studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 38 publications
2
58
2
Order By: Relevance
“…Interestingly, sexual minorities who are evangelical or attend evangelical institutions do not report higher levels of depression and social anxiety than those at other religious institutions (Wolff et al, 2016). They posit that these students' religious beliefs are likely aligned with the institution and along with Yarhouse et al (2009) suggest that "religion may offer a substantial amount of comfort and source of community to many sexual minority (SM) individuals who find incongruence with their sexual orientation and their faith" (Wolff et al, 2016, p. 209).…”
Section: Campus Climatementioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, sexual minorities who are evangelical or attend evangelical institutions do not report higher levels of depression and social anxiety than those at other religious institutions (Wolff et al, 2016). They posit that these students' religious beliefs are likely aligned with the institution and along with Yarhouse et al (2009) suggest that "religion may offer a substantial amount of comfort and source of community to many sexual minority (SM) individuals who find incongruence with their sexual orientation and their faith" (Wolff et al, 2016, p. 209).…”
Section: Campus Climatementioning
confidence: 99%
“…Sexual minority students at non-affirming religious institutions who experience bullying reported higher levels of depression (Wolff, Himes, Soares, & Miller Kwon, 2016); this is particularly troubling in light of the fact that 37% of the students in this study reported bullying compared to 27% of all students nationally (Rankin, Weber, Blumenfeld, & Frazer, 2010, as cited in Wolff et al, 2016). In contrast, the Watson (2015) study of microaggressive behavior found that, while such behavior was present, bullying and physical aggression were the least mentioned type of experience.…”
Section: Campus Climatementioning
confidence: 99%
See 3 more Smart Citations